SRC-3/AIB1: transcriptional coactivator in oncogenesis - Yan Jun; Tsai Sophia Y; Tsai Ming-jer (Acta Pharmacologica Sinica, 2016)
Steroid receptor coactivator-3 (SRC-3, also known as NCoA3, AIB1, p/CIP, RAC3, ACTR, and TRAM1), localized on a frequently amplified region, 20q12, has been associated with multiple cancers, including breast, gastric and prostate cancers. Although SRC-3 has been implicated as an oncogene, compelling evidence has only recently emerged implicating it as a causal factor in the genesis of human cancers. Here, we summarize recent evidence that indicates aberrant SRC-3 expression is important in hormone-sensitive and -insensitive human cancers.